2005
DOI: 10.1167/iovs.03-0518
|View full text |Cite
|
Sign up to set email alerts
|

Glial Remodeling and Neural Plasticity in Human Retinal Detachment with Proliferative Vitreoretinopathy

Abstract: The neural and glial components of detached neurosensory retina complicated by PVR exhibit pathology that changes characteristically with increasing detachment severity. Even in advanced degeneration, most of the structural motifs necessary for functional recovery are retained. Evidence of remodeling in the first-, second-, and third-order neurons of detached adult human retina may represent an attempt to re-establish synaptic connectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(147 citation statements)
references
References 64 publications
11
135
1
Order By: Relevance
“…3D). Redistribution of short-wavelength cone opsin in this manner has previously been reported in photoreceptor cells undergoing degenerative changes, and the labeling of the entire cell for opsin is also a feature of early human retinal detachment (26) as well as other retinal degenerations. Rod opsin was distributed normally in the OSs in both knockout (Fig.…”
Section: Cfh-deficient Aged Mice Exhibit Increased Subretinal Autoflusupporting
confidence: 56%
See 1 more Smart Citation
“…3D). Redistribution of short-wavelength cone opsin in this manner has previously been reported in photoreceptor cells undergoing degenerative changes, and the labeling of the entire cell for opsin is also a feature of early human retinal detachment (26) as well as other retinal degenerations. Rod opsin was distributed normally in the OSs in both knockout (Fig.…”
Section: Cfh-deficient Aged Mice Exhibit Increased Subretinal Autoflusupporting
confidence: 56%
“…3H). Extension of bipolar cell dendrites into the outer nuclear layer is a recognized feature of clinical and experimental retinal degeneration (26,27), and it has been suggested that as axon terminals withdraw to the cell bodies in stressed photoreceptors, secondorder neurons respond by extending processes in an attempt to maintain synaptic and trophic contact. The presence of C3 in the neuroretina is likely to result in immune-mediated damage to the retina and in the functional changes observed in this study.…”
Section: Cfh-deficient Aged Mice Exhibit Increased Subretinal Autoflumentioning
confidence: 99%
“…17,18 Furthermore, RPE proliferation with loss of surface polarity and Muller cell proliferation has also been described in the subretinal space. 17,19 All these changes persisted, to some extent, in the reattached retina and have been described as having a 'patchwork' appearance. 20 This refers to the fact that the anatomical recovery across the RPE is not uniform, and some areas may lag behind others in forming a close photoreceptor-RPE apposition.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging such conserved "off-shelf" stresshandling mechanisms might benefit some situations, while in other situations, it might be detrimental. The latter can be the case, e.g., with a profound astroglial and inflammatory response with cytokine and chemokine production in retinal detachment-induced photoreceptor degeneration (211), where attenuated reactive response of astrocytes and Mül-ler cells in GFAP Ϫ/Ϫ Vim Ϫ/Ϫ mice (116,156) reduces Erk and c-fos activation, prevents the upregulation of MCP-1 and recruitment of monocytes to the injury site, and results in reduced photoreceptor degeneration (156). Therapeutic activation of specific stress-handling mechanisms that are not normally activated in a given disease context, or suppression of unwanted stress responses, can bring therapeutic benefits and be important both for treatment and prevention.…”
Section: What Nature Addressed Well and The Windows Of Therapeutimentioning
confidence: 99%